2004
DOI: 10.1063/1.1806559
|View full text |Cite
|
Sign up to set email alerts
|

Highly flexible transparent electrodes for organic light-emitting diode-based displays

Abstract: Multilayer indium-tin-oxide (ITO)–Ag–ITO stacks were evaluated as transparent conductors for flexible organic light-emitting diode (OLED) displays. The ITO–metal–ITO (IMI) samples exhibited significantly reduced sheet resistance over ITO and greater than 80% optical transmission. The IMI films deposited on plastic substrates showed dramatically improved mechanical properties when subjected to bending both as a function of radius of curvature as well as number of cycles to a fixed radius. OLEDs were fabricated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
149
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(161 citation statements)
references
References 16 publications
3
149
1
Order By: Relevance
“…The conventional transparent and conductive thin films, such as indium tin oxide (ITO), are brittle. When deposited on flexible substrates, the conductivity of those thin film electrodes tends to deteriorate significantly after subjecting to thermal and/or mechanical strain [1][2][3]. For instance, Na et al [1] found that the resistance of ITO on Polyethylene Terephthalate (PET), increased by ∼40 times after ∼ 2500 bending cycles at a radius of ∼8 mm.…”
mentioning
confidence: 99%
“…The conventional transparent and conductive thin films, such as indium tin oxide (ITO), are brittle. When deposited on flexible substrates, the conductivity of those thin film electrodes tends to deteriorate significantly after subjecting to thermal and/or mechanical strain [1][2][3]. For instance, Na et al [1] found that the resistance of ITO on Polyethylene Terephthalate (PET), increased by ∼40 times after ∼ 2500 bending cycles at a radius of ∼8 mm.…”
mentioning
confidence: 99%
“…[1][2][3] One common route is to use films made by a disordered network of carbon nanotubes ͑NTs͒. [4][5][6][7][8][9] In this case, electrons move across the entire film by moving between NT in close proximity.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Metallic nanowires ͑NW͒ are the most prominent materials of choice to promote electronic transport in these films. In this case, electrons move between several NW forming a disordered tunneling network which spans the entire film.…”
Section: Introductionmentioning
confidence: 99%